THE IMPACT OF IMMUNOHISTOCHEMICAL MARKER INDICATORS ON TREATMENT OUTCOMES IN ENDOMETRIAL ATYPICAL HYPERPLASIA (World Bulletin of Public Health, 2025)
This study evaluates the impact of key immunohistochemical (IHC) markers on treatment outcomes in atypical endometrial hyperplasia (AEH), a precancerous condition associated with a significantly increased risk of progression to endometrioid adenocarcinoma. As management strategies differ considerably—ranging from fertility-sparing hormonal therapy to radical surgical intervention—identifying reliable biological predictors of treatment response is critical for personalized therapeutic decision-making. A total of 50 women with histologically confirmed AEH were included. Among them, 20 patients (40%) underwent detailed IHC profiling for Ki-67, p53, Bcl-2, estrogen receptors (ER), and progesterone receptors (PR). Marker expression was evaluated semi-quantitatively according to ESGO/ESMO recommendations. Treatment strategies were individualized based on clinical characteristics, reproductive goals, and biological phenotype; hormonal therapy was offered to suitable candidates, while high-risk patients received surgical management.